Review of the concept of strategy in the process of second language acquisition and learning in the light of new research lines - Álvarez, Ana María Cea (2017)
This paper focuses on the efforts made in the area of second language acquisition in order to describe the psycholinguistic mechanisms implemented by the student during the learning process. Those mechanisms, identified initially by strategies, were studied by different researchers when it was found that the strategic competence was an essential part of the student’s communicative competence. From a diachronical perspective, the notion of strategy will be reviewed, together with its different typologies and its importance in the context of a pedagogy for autonomy, where the development of a self-regulation process plays an essential part of the second language learning process.